Fundamentals of Risk Analysis and Risk Management - Molak, Vlasta (CRC Press, 2009)
Read it Online! This book bridges the gap between the many different disciplines used in applications of risk analysis to real world problems. Contributed by some of the world's leading experts, it creates a common information base and language for all risk analysis practitioners, risk managers, and decision makers.